The Role of 12/14F Ureteral Access Sheath in Flexible Ureteroscopy for Moderate Nephrolithiasis - Ozimek, Tomasz; Dellas, Pauline; Becker, Benedikt; Miernik, Arkadiusz; Roesch, Marie Christine; Merseburger, Axel Stuart; Kramer, Mario Wolfgang; Wießmeyer, Judith Riccarda (Aktuelle Urologie, 2023)
The aim was a retrospective analysis of 12/14F ureteral access sheath (UAS) usage on perioperative outcomes in patients with moderate nephrolithiasis (MN). MN was defined as a maximum of two unilateral kidney stones with a maximum stone diameter of 6–10 mm.We conducted a monocentric retrospective univariate and multivariate analysis of flexible ureteroscopies (fURS) performed for MN between 01/2014 and 12/2018.A total of 402 fURS were performed in patients with urolithiasis; 112 MN cases underwent further analysis. UAS was successfully applied in 33 MN cases [33/112 (29.46%)]. UAS was inserted regardless of the maximum kidney stone diameter and the presence of multiple kidney stones (p > 0.05). Univariate analysis revealed a prolonged median operation time (UAS: 94 min, non-UAS: 74 min, p = 0.04) and median fluoroscopy time (UAS: 75 s, non-UAS: 57.5 s, p = 0.04) in the UAS cohort. These differences were not confirmed on multivariate logistic regression.UAS was not associated with better stone-free rates in either the univariate or multivariate analysis (UAS: 26/33, non-UAS: 61/79, p = 1.0) nor with the occurrence of Clavien-Dindo ≥2 complications (UAS: 3/33, non-UAS: 9/79, p = 0.98) or median length of hospital stay (UAS: 2 days, non-UAS: 2 days, p = 0.169).We identified no statistical benefits from the usage of 12/14F UAS for MN. As no relevant UAS-associated complications were documented, both strategies (with and without UAS) are feasible.
Keywords: ureteroscopy; flexible ureteroscopy; kidney stones; stone therapy; ureteral access sheath